ARAHAN PENGENDALIAN PERUBAHAN PENGGUNAAN LAHAN MENGGUNAKAN MARKOV - CELLULAR AUTOMATA DI KABUPATEN CIANJUR - Rani Yudarwati; Santun R.P Sitorus; Khursatul Munibah (Diponegoro University, 2016)
Controlling the rate of land use change is necessary due to maintaining environment sustainability. One of the efforts is studying the changes that occur in the past few years. These changes can be studied by Markov - Cellular Automata model.Cianjur is one of the regency that has a high risk of landslide hazard, so it is necessary to control land use change in order to realize environmental sustainability in accordance with the spatial plan of Cianjur regency (RTRW). The purpose of this study was to see land use changes that occurred and evaluated with the spatial plan (RTRW) and also to conduct controlling scenarios of land use changes. The analysis showed that Cianjur regency has drastically decreased in forest area up to 10,3% and landuse inconsistencyof 10,4%. The prediction results showed that landuse change without intervention would dramatically increase inconsistency up to 20,5%. Land use scenario of restoring forest could reduce inconsistency up to 16,6%.